Clinical perspectives of anterior inferior cerebellar artery: a review - Swain, Santosh Kumar; Baliarsingh, Prasenjit (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
The anterior inferior cerebellar artery arises at the cerebellopontine angle (CPA), usually from the lower one third of the basilar artery. However, the vascular anatomy of the anterior inferior cerebellar artery (AICA) is highly variable. In respect to the neurovascular relationship in the internal auditory canal (IAC), the AICA is intimately related with vestibulocochlear and facial nerve. Microvascular compression of the vestibulocochlear nerve by AICA is an important etiology for tinnitus, hearing loss and vertigo. The vascular loop or aneurysm of the AICA will compress the vestibulocochlear nerve in the internal auditory canal. The AICA loop should be separated from the vestibulocochlear nerve. Magnetic resonance angiography (MRA) is helpful to reveal the vascular pathology of the AICA and confirm the causes for disabling otological symptoms. After confirmation of the vascular pathology of AICA, surgery is usually planned. The intrameatal AICA and vestibulocochlear nerve conflict produce specific pathological features and their surgical treatment is also invariably challenging. The objective of this review article is to discuss the details of vascular anatomy, etiopathology, clinical presentations, diagnosis, neurophysiology and current treatment of the vascular anomalies of AICA in IAC which often pose challenge to the clinicians.